Identification of domains in canine parvovirus VP2 essential for the assembly of virus-like particles. - Hurtado, A (1996)
Canine parvovirus capsids are composed of 60 copies of VP2 and 6 to 10 copies of VPl. To locate essential sites of interaction between VP2 monomers, we have analyzed the effects of a number of VP2 deletion mutants representing the amino terminus and the four major loops of the surface, using as an assay the formation of virus-like particles (VLPs) expressed by recombinant baculoviruses. For the amino terminus we constructed three mutants with progressively larger deletions, i.e., 9, 14, and 24 amino acids. Deletions of 9 and 14 amino acids did not affect the morphology and assembly capabilities of the mutants. However, the mutant with the 24-amino-acid deletion did not show hemagglutination properties or correct VLP morphology, stressing again the relevance of the RNER domain in canine parvovirus functionality. Three of the four mutants with deletions in the loops failed to make correct VLPs, indicating that these regions are essential for correct capsid assembly and morphology. Only the mutant with the deletion in loop 2 was able to assemble in regular VLPs, suggesting that this loop has little or no effect in capsid morphogenesis. Further research has demonstrated that this region can tolerate the insertion of foreign epitopes that are correctly exposed in the surface of the capsid. This result opens the door to the use of these VLPs for antigen delivery.